2011
DOI: 10.1088/0004-637x/744/1/52
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Common Envelope Phase of a Red Giant Using Smoothed-Particle Hydrodynamics and Uniform-Grid Codes

Abstract: We use three-dimensional hydrodynamical simulations to study the rapid infall phase of the common envelope interaction of a red giant branch star of mass equal to 0.88 M and a companion star of mass ranging from 0.9 down to 0.1 M . We first compare the results obtained using two different numerical techniques with different resolutions, and find overall very good agreement. We then compare the outcomes of those simulations with observed systems thought to have gone through a common envelope. The simulations fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
357
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(385 citation statements)
references
References 50 publications
(67 reference statements)
25
357
2
1
Order By: Relevance
“…We used a modified version of the grid-based hydrodynamics code enzo (O'Shea et al 2004;Passy et al 2012a;Bryan et al 2014) to run the hydrodynamics simulations. The calculations were performed on a 256 3 grid in the adiabatic approximation with outflow boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a modified version of the grid-based hydrodynamics code enzo (O'Shea et al 2004;Passy et al 2012a;Bryan et al 2014) to run the hydrodynamics simulations. The calculations were performed on a 256 3 grid in the adiabatic approximation with outflow boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The gravitational drag is instead due to gravitational forces between the gas flowing past the planet and the planet itself. Although there is no accurate expression for the gravitational drag in the presence of a density gradient (MacLeod & Ramirez-Ruiz 2015), an approximate expression can be found in Iben & Livio (1993) and Passy et al (2012a):…”
Section: Gravitational Vs Hydrodynamic Dragmentioning
confidence: 99%
“…On the other hand, Sandquist et al (1998) estimate that the overall timescale of the process lasts ∼200 days, while De Marco et al (2003) derived timescales of 9−18 yrs until a negligible amount of material remained in the envelope. The numerical simulations by Passy et al (2012), on the other hand, indicate a typical timescale of 100−200 days. Since the gravitational potential energy of the companion star scales as a −1 , where a denotes its distance from the core of the red giant, the energy deposition rate in a given range da scales as a −2 .…”
Section: Introductionmentioning
confidence: 98%
“…Also, Bobrick et al (2017), found that jet appearance and quenching during CE can produce transient objects. Other 3D studies focused on the formation of degenerate stars (Sandquist, Taam, & Burkert 2000), the formation of Wolf-Rayet stars (De Marco et al 2003), and the interaction of stellar objects within the CE phase, either by employing Eulerian (Ricker & Taam 2008, 2012 or Lagrangian (Passy et al 2012) meshes.…”
Section: Introductionmentioning
confidence: 99%